Technosexuality from the Perspective of Forensic Medicine, Imamiyya Jurisprudence, and Iranian Criminal Law - MOHAMMADSALEHI DARANI SAFORA; Abbas Jazayeri Farsani (پژوهش‌های فقهی مسائل مستحدثه)
Technosexism is a general term for sexual attraction to machines, robots, and androids, and in its specific sense, robot fetishism is a sexual orientation to humanoid robots or a sexual orientation to people who act like robots.Some moralists consider sex robots to have some functions of respecting the freedom of choice of the individual; a suitable alternative to marriage for people who are unable to form a family and treating some sexually transmitted diseases, but most of them believe that due to more negative effects, including; an instrumental view of women, a weakening of the concept of man and human relationships; a lack of sense of responsibility resulting from forming a family; along with legal morality and religious considerations, they are considered an immoral option.Their users often have physical, sexual, or psychological problems, and are likely to commit crimes such as rape, child abuse, and sexual violence due to unrealistic persuasion, increased feelings of loneliness, facilitating fantasies of sexual assault, and the implementation of pornographic fantasies. The health status of these individuals will be examined by a forensic physician to determine the level of criminal responsibility. Imami jurisprudence considers the use of sex robots to be forbidden and considered masturbation, but Iran's criminal law has remained silent on this issue. The legal systems of Canada and the United States, following the criminalization of the import of such robots, have prevented their promotion and use except in essential cases, such as helping to treat patients with disabilities or sexual defects. Therefore, it is appropriate that transparency and criminalization be implemented in the Iranian criminal system as well.